Burma's military secrets signals intelligence (SIGINT) from the Second World War to civil war and cyber warfare - Ball, Desmond (White Lotus, 1998)
This first book on signals warfare provides a unique view into all of the important military and political developments in Burma over the past half century based on the most secret and authoritative intelligence sources, i.e., signals intelligence (SIGINT) which involves radio interception, telecommunications surveillance, crypt analysis or code-breaking, and analysis of supposedly confidential signals. This book is filled with fascinating and explosive revelations about many important issues, such as: • the special relationship between Burma and China. Over the past decades, China has become Burma's principal ally, major arms supplier, and only secret intelligence partner. • the opium and heroin trade. Burma now accounts for two-thirds of the world's total production of heroin and the drug armies maintain sophisticated intelligence collection and communications systems. • the SIGINT activities of the ethnic insurgent organizations, such as the Karen National Army. • the battles at Manerplaw and Kawmura in January-February 1995, which involved some 15,000-20, 000 troops, and which resulted in the loss of these strongholds to the Burmese Army. • the use of electronic surveillance by the military junta in Rangoon to control dissent and rebellion. • the organization of Burma's security and intelligence establishment, including the dreaded Military Intelligence Service (MIS) headed by Khin Nyunt, and the new Cyber Warfare Department. • the build-up of Burma's conventional arms capabilities, giving it the largest armed forces in Asia by the turn of the century.